Faktor Penghambat Pelaksanaan Program Bimbingan Konseling di SMP Muhammadiyah 57 Medan - Adinda Alvina Wahyuni; Yenti Arsini; Ayu Rahmawati Siregar (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The purpose of this research is to find out what are the inhibiting factors for the implementation of the Counseling Guidance program at Muhammadiyah 57 Middle School Medan. The approach to this study uses qualitative descriptive research and the type of research is case study. Data collection is by interview. Data analysis techniques in this research use miles and huberman with data reduction models, presentations, and concluded the results of the study. Respondents in this study were guidance counseling teachers at Muhammadiyah 57 Middle School Medan.